Content of Heavy Metals in the Lichens of Winter Reindeer Pastures of the Timan and Bolshezemelskaya Tundras - Marija Menshakova; Miłosz Huber; Ramziya Gainanova; Valeriia Surovets; Nina Moiseeva; Anastasiia Nizikova; Marina Mashinets (Agriculture, 2022)
This article is devoted to the study of the contents of zinc, cadmium, copper, and lead in lichen in the pastures of reindeer studs in the Timan and Bolshezemelskaya tundras. These areas are located in the Arctic part of Russia, to the west of the Polar Urals. These are areas where carbonate and sandstone rocks of the Permian–Mesozoic age dominate under the soil cover, as well as older deposits located in the western part of the research area (dated to the Cambrian–Devonian period). In these rocks, there is mineralization with metals, including copper. Research carried out in 2018 showed that in the surface layer of lichens, the concentration of metals was assessed differently in the upper, middle, and lower parts of the hill. On this basis, it was possible to identify clean and contaminated pastures. The high copper content in some pastures can be explained by the migration of metal ions from the parent rock. Due to the similar ionic radius of copper and the higher electrocativity in relation to zinc, the metal was probably displaced in the lichen. The observed concentrations can cause high levels of metals in the tissues and organs of deer. A high content of metals in lichens was found in samples collected near industrial enterprises, as well as at a considerable distance from them. At the same time, lichens at some locations near boiler houses or oil rigs are quite pure. In this regard, it has been suggested that the source of pollutants can be either natural factors (copper-bearing sands) or the ingress of metals from a remotely located source.